The effect of experimentally-induced subacromial pain on proprioception. Issue 1 (February 2015) - Sole, Gisela; Osborne, Hamish; Wassinger, Craig
Abstract Shoulder injuries may be associated with proprioceptive deficits, however, it is unknown whether these changes are due to the experience of pain, tissue damage, or a combination of these. The aim of this study was to investigate the effect of experimentally-induced sub-acromial pain on proprioceptive variables. Sub-acromial pain was induced via hypertonic saline injection in 20 healthy participants. Passive joint replication (PJR) and threshold to detection of movement direction (TTDMD) were assessed with a Biodex System 3 Pro isokinetic dynamometer for baseline control, experimental pain and recovery control conditions with a starting position of 60° shoulder abduction. The target angle for PJR was 60° external rotation, starting from 40°. TTDMD was tested from a position of 20° external rotation. Repeated measures ANOVAs were used to determine differences between PJR absolute and variable errors and TTDMD for the control and experimental conditions. Pain was elicited with a median 7 on the Numeric Pain Rating Scale. TTDMD was significantly decreased for the experimental pain condition compared to baseline and recovery conditions (≈30%, P = 0.003). No significant differences were found for absolute (P = 0.152) and variable (P = 0.514) error for PJR. Movement sense was enhanced for the experimental sub-acromial pain condition, which may reflect protective effects of the central nervous system in response to the pain. Where decreased passive proprioception is observed in shoulders with injuries, these may be due to a combination of peripheral tissue injury and neural adaptations that differ from those due to acute pain.